Biodiversity of the Ediacaran-early Cambrian transition in northwestern Argentina and related areas - Aceñolaza, Florencio Gilberto (2012)
The Ediacaran-early Cambrian is a significant time of geological history in terms of biodiversity dynamics. During this time-span a particular soft-bodied fauna developed and disappeared, being replaced by the emergent skeleton-bearing faunas. This very special feature not only gave rise to an abundant fossil record but also triggered the bioturbation of strata, thus generating the “agronomic revolution” – comparable to the revolution produced by mankind upon discovery of the possibilities offered by agriculture. Several outcrops of rocks from that period in northwestern Argentina provide examples spurring a general overview of the major evolutionary trends in the Ediacaran-lower Cambrian seas of the region.